Adaptive Pedagogical Approaches for Inclusive Education: A Framework for Policy and Practice Integration - Herlina Yuni Setyowati; Artha Roichatul Jannah; Dhinar Wahyu Ilahi; Ajeng Widyarini (Universitas Negeri Surabaya, 2025)
Inclusive education is a fundamental right for every child, including those with special needs, and is governed by various national and international regulations. In Indonesia, the implementation of inclusive education is regulated by Law No. 20 of 2003 on the National Education System, Ministry of National Education Regulation No. 70 of 2009 on Inclusive Education, and Ministry of Education and Culture Regulation No. 6 of 2018 on the Organization of Inclusive Schools. This study aims to explore effective learning strategies for children with special needs in inclusive school settings, within the framework of the existing legal provisions. A qualitative literature review method was employed to examine various policies and inclusive teaching models. The findings indicate that effective instructional strategies include differentiated instruction, curriculum adaptation, the use of assistive technology, and collaborative efforts among teachers, parents, and professionals. The implementation of these strategies must align with the principles of non-discrimination, accessibility, and equity as mandated by law. Key challenges in implementation include limited infrastructure, insufficient teacher competencies, and the lack of widespread dissemination of relevant regulations. Therefore, collaboration among government entities, schools, and communities is essential to ensure the fulfillment of the right to inclusive education for children with special needs in accordance with the prevailing legal framework. Keywords: Inclusive Education, Children with Special Needs, Learning Strategies, Educational Policy, National Education Law.